A New Theoretical Model for Depicting Profit Optimality - Spitz, A. Edward; DeKorvin, Andre (Journal of Financial and Quantitative Analysis, 1971)
Each business firm has a large body of fundamental data that can be organized so that it can aid in graphically determining the firm's optimum profit. In this paper an attempt has been made to bring forth a method by which some choice of policy may be followed in order to select a particular profit curve. More precisely, a policy will be determined that leads to a given optimal profit curve. In this paper “optimal profit curve” will mean the profit curve that has been selected from a fixed set of possible profit curves. The purpose of the paper is to describe a method to determine the policy that will reduce the optimal curve. The method is based on a general form of the Riesz- Kakutani Representation Theorem, which states that a bounded linear operator from the space of continuous functions of one variable t where 0 ≤ t ≤ 1 to the space of continuous functions can be represented as an integral to a Gowurin measure.